CZY POTRZEBA NAM AUTORYTETÓW NA ŚWIECIE? - Kowalik, Stanisław (Wydział Prawa i Administracji UAM, 2006)
The common belief among Poles today is that we are living in a world in which authorities have undergone a certain crisis. An attempt to verify this conviction has been made. The author has analysed certain concepts of social and personal authorities. The findings show that although there exist (realistic) reasons why social authorities are not readily commonly recognised today, there is no theoretical explanation or any empirical findings that would confirm a decline of the significance of personal authorities in people's lives, and in particular in the lives of the young ones. At the same time the author suggests that current substitutes of authorities, such as idols, living legends, people attaining mythical status are unable to make up for the need for genuine social authorities.
DO WE NEED AUTHORITIES IN TODAY’S WORLD?